Divergent Mast Cell Responses Modulate Antiviral Immunity During Influenza Virus Infection - Murphy-Schafer, Ashleigh R.; Paust, Silke (Frontiers in Cellular and Infection Microbiology, 2021)
Influenza A virus (IAV) is a respiratory pathogen that infects millions of people each year. Both seasonal and pandemic strains of IAV are capable of causing severe respiratory disease with a high risk of respiratory failure and opportunistic secondary infection. A strong inflammatory cytokine response is a hallmark of severe IAV infection. The widespread tissue damage and edema in the lung during severe influenza is largely attributed to an overexuberant production of inflammatory cytokines and cell killing by resident and infiltrating leukocytes. Mast cells (MCs) are a sentinel hematopoietic cell type situated at mucosal sites, including the lung. Poised to react immediately upon detecting infection, MCs produce a vast array of immune-modulating molecules, including inflammatory cytokines, chemokines, and proteases. As such, MCs have been implicated as a source of the immunopathology observed in severe influenza. However, a growing body of evidence indicates that MCs play an essential role not only in inducing an inflammatory response but in suppressing inflammation as well. MC-derived immune-suppressive cytokines are essential to the resolution of a number of viral infections and other immune insults. The absence of MCs prolongs infection, exacerbates tissue damage, and contributes to the dissemination of the pathogen to other tissues. Production of cytokines such as IL-10 and IL-6 by MCs is essential for mitigating the inflammation and tissue damage caused by innate and adaptive immune cells alike. The two opposing functions of MCs—one pro-inflammatory and one anti-inflammatory—distinguish MCs as master regulators of immunity at the site of infection. Amongst the first cells to respond to infection or injury, MCs persist for the duration of the infection, modulating the recruitment, activation, and eventual suppression of other immune cells. In this review, we will discuss the immune-modulatory roles of MCs over the course of viral infection and propose that the immune-suppressive mediators produced by MCs are vital to minimizing immunopathology during influenza infection.